2015
DOI: 10.1186/s13023-014-0221-6
|View full text |Cite
|
Sign up to set email alerts
|

Gene panel sequencing in heritable thoracic aortic disorders and related entities – results of comprehensive testing in a cohort of 264 patients

Abstract: BackgroundHeritable Thoracic Aortic Disorders (H-TAD) may present clinically as part of a syndromic entity or as an isolated (nonsyndromic) manifestation. About one dozen genes are now available for clinical molecular testing. Targeted single gene testing is hampered by significant clinical overlap between syndromic H-TAD entities and the absence of discriminating features in isolated cases. Therefore panel testing of multiple genes has now emerged as the preferred approach. So far, no data on mutation detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 48 publications
3
37
0
2
Order By: Relevance
“…This emphasizes the extreme allelic heterogeneity of H‐TAD‐related disorders. Young age at diagnosis, a positive family history, and presence of syndromic features were shown to be the strongest predictors for the identification of a disease‐causing variant in the literature ( P = 0.001–0.01) (Campens et al., ). The observation that the mean age at DNA testing in the group of patients with a pathogenic or likely pathogenic variant was 11 years lower than the mean age in the groups without a pathogenic or likely pathogenic variant is in line with this.…”
Section: Discussionmentioning
confidence: 99%
“…This emphasizes the extreme allelic heterogeneity of H‐TAD‐related disorders. Young age at diagnosis, a positive family history, and presence of syndromic features were shown to be the strongest predictors for the identification of a disease‐causing variant in the literature ( P = 0.001–0.01) (Campens et al., ). The observation that the mean age at DNA testing in the group of patients with a pathogenic or likely pathogenic variant was 11 years lower than the mean age in the groups without a pathogenic or likely pathogenic variant is in line with this.…”
Section: Discussionmentioning
confidence: 99%
“…AD usually occurs in non-syndromic and sporadic form (~80%) or in association with hereditary genetic disorders, such as familial thoracic aortic dissection (fTAAD), Marfan syndrome (MFS), the vascular type of Ehlers-Danlos syndrome (EDS), Loeys-Dietz syndrome (LDS), and arterial tortuosity syndrome (ATS) (Goldfinger et al, 2014;Hoffjan, 2012;Khau Van Kien et al, 2004;Ritelli et al, 2009). Although previous genetic studies in familial AD cases have identified several genes (Table S1 in Supporting Information) responsible for this disease, large fraction of clinical cases, especially sporadic cases, still lack genetic targets (Campens et al, 2015;Guo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This explains the scarcity of mutations reported in the C-propeptide region. Previously, targeted region capture combined with next-generation sequencing was successfully utilized to uncover pathologic variants of COL3A1 in individuals with aortopathy with unsuspected vEDS (7,27). As with the proband in the present study, they were subject to targeted sequencing primarily based on aortic phenotypes, rather than other syndromic manifestations.…”
Section: Discussionmentioning
confidence: 99%